CHARACTER OF VASCULAR DISORDERS IN ADOLESCENTS WITH OSTEOARTROSIS - Lebez, I.S.; Letyago, G.V. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 1970)
The state of vascular sector of the microcirculatory system was studied by capillaroscopy of the nail matrix in 106 adolescents, aged 15-18, with OA. It was established that degenerative lesions of joints were characterized by development of various vascular changes in the microcirculatory system. The most frequent disorders were twisting of capillary branches, moderate spasm of arterial sector, a decrease in the quantity of capillary rows, and in the number of functioning capillaries in them. Besides, there was determined irregular arrangement of capillaries in the row and contraction of capillary loops. All that testified to the development of capillarotrophic insufficiency which contributes to development and progression of degenerative changes in the articular cartilage.